Deuterium retention and surface morphology modification in oxidized tungsten exposed to D plasma. (3rd September 2021) - Puyang, S.A.; Lyu, Y.M.; Nian, F.F.; Xu, Y.P.; Yang, Z.S.; Zhou, H.S.; Luo, G.-N.
Abstract: Tungsten (W) is the most promising plasma facing material in future fusion reactor. However, oxidation occurs readily on W and might influence the hydrogen isotopes retention behavior in W. To explore the mechanism of oxidation on the hydrogen isotopes retention behavior in W, oxidized W samples have been exposed to D plasma (32.3 eV, 2 × 10 20 Dm −2 s −1 ) in a linear plasma device. Surface morphology and deuterium (D) retention behavior in W have been characterized after exposure to D plasma with fluence of 10 23 D/m 2 . After D plasma exposure, a porous layer has been found on the surface of oxidized W. The main chemical content of the porous layer is pure W. The existence of pre-oxide layer contributes the increase of retention amount of D in the form of D2 O and may contribute to the decrease of the retention amount of D in the form of HD/D2 . Highlights: Oxidation significantly influence the D retention behavior in W. A porous tungsten layer appeared in samples' surface after D plasma exposure. The size and the density of pores may influenced by the thickness of oxide layer. The increase of the thickness of oxide layer improve the release amount of D in the form of D2 O.